Association of Lameness Prevalence and Severity in Early-Lactation Cows with Milk Traits, Metabolic Profile, and Dry Period - Vigilijus Jukna; Edita Meškinytė; Gediminas Urbonavičius; Ronaldas Bilskis; Ramūnas Antanaitis; Lina Kajokienė; Vida Juozaitienė (Agriculture)
This study investigated the prevalence and severity of lameness in dairy cow herds, focusing on its relationship with milk traits, metabolic profile, and dry period management. Lameness was evaluated in 4221 multiparous Holstein dairy cows during early lactation (up to 60 days postpartum) using a 1-to-5 scale. The average lameness score was 1.67, with a prevalence of 10.66% (scores 3 to 5) and 4.55% classified as severe (scores 4 to 5). Severe lameness was associated with energy-corrected milk losses of −11.00 kg/day (p < 0.001) and a decrease in milk lactose concentration by −0.16 percentage points (p < 0.001), alongside a rise in somatic cell scores by +0.11. The incidence of cows with a milk fat-to-protein ratio below 1.2 increased by 21.7 percentage points, while those with a ratio above 1.4 rose by 19.1 percentage points as lameness worsened. Additionally, non-esterified fatty acid concentrations increased by 1.46 times as lameness severity intensified (p < 0.001). Cows without lameness had blood cortisol levels 1.86 times lower than affected cows, with cortisol tripling in those with the highest scores. A dry period of 30 to 60 days was correlated with more healthy cows, whereas periods over 90 days resulted in 1.586 times higher odds of lameness (p < 0.05). This research underscores the need for improved management strategies to enhance dairy cow welfare and productivity.